Proceedings of the Twenty-Eighth Annual ACM-SIAM Symposium on Discrete Algorithms 2017
DOI: 10.1137/1.9781611974782.100
|View full text |Cite
|
Sign up to set email alerts
|

Polynomial Kernels and Wideness Properties of Nowhere Dense Graph Classes

Abstract: Nowhere dense classes of graphs [21,22] are very general classes of uniformly sparse graphs with several seemingly unrelated characterisations. From an algorithmic perspective, a characterisation of these classes in terms of uniform quasi-wideness, a concept originating in finite model theory, has proved to be particularly useful. Uniform quasi-wideness is used in many fpt-algorithms on nowhere dense classes. However, the existing constructions showing the equivalence of nowhere denseness and uniform quasi-wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(47 citation statements)
references
References 25 publications
0
47
0
Order By: Relevance
“…Uniform quasi-wideness was introduced by Dawar in [19] and it was proved by Nešetřil and Ossona de Mendez in [60] that uniform quasi-wideness is equivalent to nowhere denseness. Very recently, it was shown that the function N in the above definition can be chosen to be polynomial in m [45,70]. A single exponential dependency was earlier established for classes of bounded expansion [44].…”
Section: Uniform Quasi-widenessmentioning
confidence: 99%
“…Uniform quasi-wideness was introduced by Dawar in [19] and it was proved by Nešetřil and Ossona de Mendez in [60] that uniform quasi-wideness is equivalent to nowhere denseness. Very recently, it was shown that the function N in the above definition can be chosen to be polynomial in m [45,70]. A single exponential dependency was earlier established for classes of bounded expansion [44].…”
Section: Uniform Quasi-widenessmentioning
confidence: 99%
“…For instance, consider the problem of computing the smallest distance-r dominating set in a given graph G, which is a subset of vertices D such that every vertex of G is at distance at most r from some vertex of D. This problem often serves as a benchmark for sparsity methods, and it was considered in the theory of sparse graphs from the points of view of parameterized algorithms [12], approximation [1,18], and kernelization [14,19,29]. In particular, Amiri et al [1] have recently used the results of Nešetřil and Ossona de Mendez [35] to give a distributed logarithmic-time constant-factor approximation algorithm for the distance-r dominating set problem on any class of bounded expansion.…”
Section: Introductionmentioning
confidence: 99%
“…For us it will be important that the function N can be assumed to be polynomial in m (the degree of the polynomial may depend on r) and that the sets B and S can be efficiently computed. Polynomial bounds were first obtainend by Kreutzer et al [28], we refer to the improved bounds of Pilipczuk et al [39].…”
Section: Preliminariesmentioning
confidence: 99%
“…It was then shown that nowhere dense classes are the limit of tractability based on sparsity methods, more precisely, it was shown in [13] that if a class C is not nowhere dense and closed under taking subgraphs, then there is some r 1 such that Distance-r Dominating Set on C is W[2]-hard. It was later shown that the problem admits a polynomial kernel [28] and in fact an almost linear kernel [14] on nowhere dense classes.…”
Section: Introductionmentioning
confidence: 99%